PENGARUH PENGUNGKAPAN LAPORAN BERKELANJUTAN TERHADAP KINERJA KEUANGAN DENGAN VARIABEL PEMODERASI UKURAN PERUSAHAAN (EMITEN ENERGY BURSA EFEK INDONESIA PERIODE 2021-2023) - Adisti, Aprilia Zahra; Mukti, Aloysius Harry; Eprianto, Idel (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The research aims to examine the effect of Sustainability Report Disclosure on Financial Performance with the moderating variable Company size. The research population is all energy issuers on the Indonesian Stock Exchange for the 2021-2023 period. The variable used is Financial Performance as the dependent variable, Sustainability Report Disclosure as an independent variable, and Company Size as a moderation variable. The sampling technique used was the purposive sampling method, and a total of 44 samples of issuers were obtained. The analytical methods used are descriptive statistical analysis, classical assumptions, multiple linear analysis, moderated regression analysis, and hypothesis testing. The results of this research show that partial Sustainability Report Disclosure has a negative effect on Financial Performance and Company Size has a positive effect on Financial Performance. The results of this research for the moderating variable, namely Company Size, are able to moderate (strengthen) the negative influence of Sustainable Report Disclosure on Financial Performance.